2004
DOI: 10.1111/j.1523-1755.2004.00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor tyrosine kinase inhibition is not protective in PCK rats

Abstract: EGFR tyrosine kinase inhibition did not protect PCK rats from the development of PKD. This may be due to effects on collecting duct cAMP that counteract possible beneficial effects on the extracellular-regulated protein kinase (ERK)/mitogen-activated protein kinase (MAPK) pathway, particularly in the absence of EGFR overexpression or mislocalization. The relevance of these observations to the treatment of human cystic kidney diseases deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 56 publications
2
46
2
2
Order By: Relevance
“…25 VPV2R and cAMP levels are elevated in the kidneys of PCK rats. 26 In addition, EGFR tyrosine kinase inhibition had no beneficial effect on the PKD of the PCK rat in our experiments as well as in those reported by others. 26 Therefore, the expression of p-ERK1/2 in the kidney cyst lining epithelial cells of the PCK rat may be associated with the cAMP pathway, not with the EGF/ TGF-␣/EGFR pathway.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…25 VPV2R and cAMP levels are elevated in the kidneys of PCK rats. 26 In addition, EGFR tyrosine kinase inhibition had no beneficial effect on the PKD of the PCK rat in our experiments as well as in those reported by others. 26 Therefore, the expression of p-ERK1/2 in the kidney cyst lining epithelial cells of the PCK rat may be associated with the cAMP pathway, not with the EGF/ TGF-␣/EGFR pathway.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies showed that treatment of the PCK rat with EGFR tyrosine kinase inhibitors, EKI-785 and EKB-569, led to mild, but not significant, improvement in the liver cyst volume. 26 In this study, p-EGFR was undetectable in the liver after gefitinib treatment, but immunostaining showed that p-ERK1/2 was persistently expressed in the BECs of PCK rats after treatment. Although a number of studies have implicated the importance of the EGF/TGF-␣/EGFR pathway in the pathogenesis of PKD, the proliferation of cholangiocytes seems not to be simply mediated by this pathway.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…57 Treatment with EGFR tyrosine kinase inhibitors inhibits renal cyst growth in several PKD rodent models, 58,59 but not all. 60 The EGFR and Src interact with each other, Src can phosphorylate multiple tyrosine residues of the EGFR, and both kinases are thought to be able to mutually activate each other. 61 STAT3 activation in response to EGFR signaling requires Src.…”
Section: Discussionmentioning
confidence: 99%
“…For renal cAMP estimations, a cAMP ELISA system without acetylation (Biomedical Technologies, Stoughton, MA) was used. Results from both assays were expressed per wet weight of tissue (15,35).…”
Section: Elisa Of Et-1 and Campmentioning
confidence: 99%